2019
DOI: 10.3389/fimmu.2019.02605
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Assisted Definition of the Inflammatory Infiltrates in Patients With Different Categories of Banff Kidney Allograft Rejection

Abstract: Currently, the diagnosis of kidney allograft rejection relies on individual histological assessments made by expert pathologists according to the Banff classification. In this study, we applied new Computer-Assisted System Technology (newCAST™) by Visiopharm® with the aim of identifying and quantifying the immune cells in inflammatory infiltrates. We searched for distinctive cellular profiles that could be assigned to each rejection category of the Banff schema: antibody-mediated rejection (active and chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…46 Two other multiplex studies found similar results in acute and chronic ABMR, and in addition highlighted heterogeneity in B-cell infiltration. 47,48 Finally, plasma cellrich infiltrates have been reported across ABMR and TCMR, where they confer markedly worse allograft survival. 49 Taken together, although cell type abundance in rejection does not necessarily correlate with the initial trigger, these interindividual differences indicate that reducing tubulointerstitial inflammation and microvascular inflammation to either "T-cell mediated" or "antibody mediated" does not represent the complexity of ongoing immune processes.…”
Section: Variations In the Infiltrating Immune Cell Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Two other multiplex studies found similar results in acute and chronic ABMR, and in addition highlighted heterogeneity in B-cell infiltration. 47,48 Finally, plasma cellrich infiltrates have been reported across ABMR and TCMR, where they confer markedly worse allograft survival. 49 Taken together, although cell type abundance in rejection does not necessarily correlate with the initial trigger, these interindividual differences indicate that reducing tubulointerstitial inflammation and microvascular inflammation to either "T-cell mediated" or "antibody mediated" does not represent the complexity of ongoing immune processes.…”
Section: Variations In the Infiltrating Immune Cell Compositionmentioning
confidence: 99%
“…First, immunohistochemical studies revealed that NK cells constitute a varying minority of the inflammatory infiltrate in biopsies with microvascular inflammation, which is predominated mainly by macrophages and T cells. 16,46,47,167 If NK cells are a main orchestrator in the pathogenesis of microvascular inflammation, one would expect more consistent intragraft populations. Second, it is clear that missing self is neither sufficient nor necessary to develop microvascular inflammation, given that many patients with missing self never develop this phenotype, and that HLA-DSA-negative cases of microvascular inflammation can be observed in the absence of missing self.…”
Section: Analogymentioning
confidence: 99%
“…Since the MCP-1 chemokine attracts both monocytes and T-cells [ 49 , 50 ], the above effect of anoxia-reoxygenation may facilitate the interaction between RPTECs and CD4+ T-cells. MCP-1 production by the RPTECs may also contribute to the observed presence of mononuclear cells, including CD4+ T-cells, inside the tubular basement membrane and in attachment with renal tubular epithelial cells in the tubulitis that characterizes kidney biopsies in acute cellular rejection [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, tubulitis characterizes the renal biopsies from patients with acute cellular rejection. In tubulitis, mononuclear cells, including CD4+ T-cells, are present inside the tubular basement membrane and in attachment with renal tubular epithelial cells [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…M1 macrophages secrete pro-inflammatory cytokines that participate in the development of chronic rejection, whereas M2 macrophages secrete anti-inflammatory cytokines to promote tissue repair or graft fibrosis through the macrophage-to-myofibroblast transition (MMT) ( 23 , 24 ). The M2 macrophages accumulation increased significantly 1–5 years after transplantation involved in the chronic injure progression ( 12 ), which may be associated with the fibrosis and decreased graft function ( 25 , 26 ). We found CD163 + M2 cells increased in CAAMR but lower than that in CAMR patients, revealed that M2 macrophages might play a more prominent role in CAMR than in CAAMR.…”
Section: Discussionmentioning
confidence: 99%